Epilepsy12—a pilot of national audit tools for childhood epilepsies. (29th September 2015) - Green, J; Dunkley, C
Abstract : Aims: To assess the management of children with seizures and suspected epilepsies against national guidance. To pilot methodology for future national audit. Methods: The population included all children who presented over a 6-month period to a district general hospital who had a subsequent EEG. Retrospective case-note analysis was undertaken on those meeting defined inclusion criteria. Twelve clinical performance indicators mapped to national guidance were applied to the first 12 months of paediatric care. Results: Conclusions: The audit provides data to supplement ongoing development of local clinical practice and epilepsy services. The pilot demonstrated EEG referrals as a practical method for cohort ascertainment across acute and non-acute settings. A short proforma enabled a standardised retrospective clinical data set to be pragmatically obtained. The total time undertaken to complete the audit by the first author (F1) was 12–15 h. The audit tool has been previously applied within a multi-cohort regional setting and introduces the possibility of longitudinal and multi-cohort comparison. The audit was undertaken to inform a successful bid to the Healthcare Quality Improvement Partnership for a 3-year national audit. The audit commenced in October 2009 and is managed by the Royal College of Paediatrics and Child Health with epilepsy action and the British Paediatric Neurology Association as partners.